Determination of in vitro genotoxic effects of pine resin and Aronia melonacarpa on prostate and breast cancer cell lines by using comet assay technique - BECEREN, AYFER; BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2022)
The cancer burden continues to grow globally and places extraordinary physical, emotional and financial pressures on individuals, communities and health systems. Studies continue without slowing down to establish new targets and treatment strategies for cancer, which still remains an important problem in the clinic and does not have a definitive cure yet. Natural compounds obtained from different sources stand out as new therapeutic agents in cancer due to their more effective and selective properties and lower toxic effects. Thus, we aimed to clarify the possible anticancer effects of Aronia melonacarpa on human breast cancer cell line (MCF-7) and pine resinon prostate cancer cell line (PC-3).Our target plants, pine resin and Aronia melonacarpa were collected from different locations from Aegean and Blacksea region of Türkiye, respectively. The genotoxic effect of the methanol extracts was determined by alkaline comet assay. 100, 200 and 400 μg/ml extract concentrations, which have the high cytotoxic effect, were used. The examined groups were control negative, plant extract and positive control groups. Comparison of the anti-cancer and genotoxic effect of different concentrations on MCF-7 of Aronia melonacarpa and pine resin on PC-3 was evaluated by SPSS 20.0 program. Comet assay results showed that the both Aronia melonacarpa and pine resin extract exhibited genotoxic effects against MCF-7 and PC-3 cell lines in a dose-dependent manner by increasing the mean percentage of DNA damage after 24hrs of treatment (p<0.001).However, the observed toxicity of this two plant extract needs to be confirmed by additional studies. Based on our results, further examination of the potential anticancer properties of two plant species and the identification of the active ingredients of these extracts is warranted. This preliminary study is important for future studies and we anticipate that it will contribute to the development of a new drug in cancer treatment.
Keywords: Eczacılık; Sağlık Bilimleri; Pharmacology and Therapeutics; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Yaşam Bilimleri; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Life Sciences